Statistical analysis of patient-reported outcome data in randomised controlled trials of locally advanced and metastatic breast cancer: a systematic review. Issue 9 (September 2018) - Pe, Madeline; Dorme, Lien; Coens, Corneel; Basch, Ethan; Calvert, Melanie; Campbell, Alicyn; Cleeland, Charles; Cocks, Kim; Collette, Laurence; Dirven, Linda; Dueck, Amylou C; Devlin, Nancy; et al.
Summary: Although patient-reported outcomes (PROs), such as health-related quality of life, are important endpoints in randomised controlled trials (RCTs), there is little consensus about the analysis, interpretation, and reporting of these data. We did a systematic review to assess the variability, quality, and standards of PRO data analyses in advanced breast cancer RCTs. We searched PubMed for English language articles published in peer-reviewed journals between Jan 1, 2001, and Oct 30, 2017. Eligible articles were those that reported PRO results from RCTs of adult patients with advanced breast cancer receiving anti-cancer treatments with reported sample sizes of at least 50 patients—66 RCTs met the selection criteria. Only eight (12%) RCTs reported a specific PRO research hypothesis. Heterogeneity in the statistical methods used to assess PRO data was observed, with a mixture of longitudinal and cross-sectional techniques. Not all articles addressed the problem of multiple testing. Fewer than half of RCTs (28 [42%]) reported the clinical significance of their findings. 48 (73%) did not report how missing data were handled. Our systematic review shows a need to improve standards in the analysis, interpretation, and reporting of PRO data in cancer RCTs. Lack of standardisation makes it difficult to draw robust conclusions and compare findings across trials. The Setting International Standards in the Analyzing Patient-Reported Outcomes and Quality of Life Data Consortium was set up to address this need and develop recommendations on the analysis of PRO data in RCTs.